2023
DOI: 10.1029/2023je007826
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Seismicity of Mars With InSight

S. Ceylan,
D. Giardini,
J. F. Clinton
et al.

Abstract: The InSight seismometers have recorded more than 1300 events. Ninety‐eight of these, named the low‐frequency family, show energy predominantly below 1 Hz down to ∼0.1 Hz. The Marsquake Service identified seismic phases and computed distances for 42 of these marsquakes, 24 of which have backazimuths. Hence, the locations of the majority of low‐frequency family events remain undetermined. Here, we use an envelope shape similarity approach to determine event classes and distances, and introduce an alternative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…Boulder tracks also suggest recent activity at Cerberus Fossae (Roberts et al., 2012; Taylor et al., 2013). The InSight Mission has shown that Cerberus Fossae is still active (Brinkman et al., 2021; Ceylan et al., 2023; Jacob et al., 2022; Perrin et al., 2022; Stähler et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boulder tracks also suggest recent activity at Cerberus Fossae (Roberts et al., 2012; Taylor et al., 2013). The InSight Mission has shown that Cerberus Fossae is still active (Brinkman et al., 2021; Ceylan et al., 2023; Jacob et al., 2022; Perrin et al., 2022; Stähler et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of global events M w ≤ 3 is similar to that of terrestrial intraplate seismic activity. Of the total recorded seismicity, more than half can be attributed to Cerberus Fossae (Ceylan et al., 2023; Jacob et al., 2022; Stähler et al., 2022). Stähler et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early 2019, it deployed the only seismic station, SEIS (Seismic Experiment for Interior Structure), to record the seismic vibrations on Mars (Lognonné et al., 2019). The InSight seismometer successfully detected ∼1,300 Marsquake events before its termination in December 2022 (Ceylan et al., 2023), providing indications of Martian tectonic activity (Ceylan et al., 2022; Drilleau et al., 2022; Giardini et al., 2020; Horleston et al., 2022; Jacob et al., 2022; Sun & Tkalčić, 2022). These seismic data have been used to determine the interior structures of the red planet at different scales using surface wave analysis (Beghein et al., 2022; Deng & Levander, 2022; Kim et al., 2022; Li et al., 2023; Xu et al., 2023), autocorrelation functions (ACFs) (Compaire et al., 2021; Deng & Levander, 2020, 2022; Qin et al., 2023; Schimmel et al., 2021), receiver functions (Knapmeyer‐Endrun et al., 2021; Lognonné et al., 2020), anisotropy analysis (Li et al., 2022), attenuation modeling (Karakostas et al., 2021) and geophysical inversion (Khan et al., 2021; Stähler et al., 2021).…”
Section: Introductionmentioning
confidence: 99%